Efektivitas Konseling Teman Sebaya Untuk Mengurangi Stres Pembimbingan Skripsi Pada Mahasiswa - Rusnawati Ellis; Prisca Diantara Sampe (Peneliti.net, 2022)
Stress is a natural part of human life that is difficult to define because every human being has different reasons when facing a problem that cannot be solved as well as the stress of thesis guidance. The research is aimed determinan to (1) the description thesis guidance stress of study; (2) the effectiveness of peer counseling to reduce thesis guidance stress of study. This research is an experimental study using the one group pretest-posttest design. The sampling technique uses purposive sampling. Data analysis using non-parametric test, namely Wilcoxon's difference test. The results of this research indicate (1) the description thesis guidance stress of guidance and counseling study program, Pattimura Univercity in the high category there are 11 students, in the medium category there are 34 students and in the low category there are 9 students;(2) peer counseling is effective in reducing thesis guidance stress of student value Asymp Sig. (2-tailed) 0.003 is smaller than <0.005, then it can be concluded that H0 is rejected and Ha is accepted